Prof. dr hab. Zbigniew Bukowski (1931–2024). Wybitny badacz pradziejowych epok metali. Przyjaciel Instytutu Archeologii UMK w Toruniu - Gackowski, Jacek (Acta Universitatis Nicolai Copernici Archeologia, 2024)
.....